Usnea in West Java: a potential source of bioactive secondary metabolites - Miftahul Jannah; Qurrota A`yun; Nida Afifah; Eko Prasetya; Muhammad Rifqi Hariri (The East Java Biological Society, 2022)
Lichen is a symbiotic organism consisting of algae (photobionts) and fungi (mycobiont). In Indonesia, Usnea is the only genus of lichen that has been widely recognized and used by the local community for traditional medicine. It is locally known as kayu angin, rusuk angin, or janggot Kai. Furthermore, it produces lichen acid and other compounds as secondary metabolites that need investigation. Therefore, this study aimed to identify species and determine the secondary metabolites of Usnea in West Java. There were 13 species of Usnea identified, with U. rubrotincta, U. mutabilis, and U. barbata being new to West Java. The extraction of U. esperantiana has the highest number of lichen acids, with 20 different types identified. This study showed that Usnea contains lichen acid, flavonoid, and saponin compounds. The secondary metabolites are a potential source of natural products for bioprospecting.